2017
DOI: 10.1109/twc.2017.2718504
|View full text |Cite
|
Sign up to set email alerts
|

Joint Load Balancing and Interference Mitigation in 5G Heterogeneous Networks

Abstract: We study the problem of joint load balancing (user association and user scheduling) and interference management (beamforming design and power allocation) in heterogeneous networks (HetNets) in which massive multiple-input multipleoutput (MIMO) macro cell base station (BS) equipped with a large number of antennas, overlaid with wireless self-backhauled small cells (SCs) are assumed. Self-backhauled SC BSs with fullduplex communication employing regular antenna arrays serve both macro users and SC users by using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 28 publications
0
94
0
Order By: Relevance
“…At the communication level, proximity-based computing and millimeter wave (mmWave) links play major roles in reducing task offloading latency from edge devices to servers by reducing distance attenuation and providing broad bandwidth with high directionality, respectively. In addition, mmWave also enables wireless backhauling [15], [16] that facilitates edge servers' prefetching popular content with low latency. At the processing level, proactive computing provides significant latency reduction while maximizing resource efficiency by avoiding repetitive and redundant on-demand computing [17]- [19].…”
Section: Low Latency Enablersmentioning
confidence: 99%
“…At the communication level, proximity-based computing and millimeter wave (mmWave) links play major roles in reducing task offloading latency from edge devices to servers by reducing distance attenuation and providing broad bandwidth with high directionality, respectively. In addition, mmWave also enables wireless backhauling [15], [16] that facilitates edge servers' prefetching popular content with low latency. At the processing level, proactive computing provides significant latency reduction while maximizing resource efficiency by avoiding repetitive and redundant on-demand computing [17]- [19].…”
Section: Low Latency Enablersmentioning
confidence: 99%
“…where A j is the set of associated aUEs with j th drone and are scheduled on same spectrum and time resources as t th tUE. The second term in (5) represents the inter-tier interference on the access transmissions of t th tUE. The received SINR at t th tUE can be expressed by:…”
Section: B Access Downlink Transmissionsmentioning
confidence: 99%
“…In this regard, 3rd Generation Partnership Project (3GPP) has introduced the integrated access and backhaul (IAB) network architecture to allow for flexible deployment of next-generation cellular networks [3], [4]. Generally, the IAB architecture implies tight interworking between access and backhaul links, where the IAB-donor (i.e., macro base station (MBS)) uses the same infrastructure and wireless channel resources to provide access and backhauling functionalities for cellular users and IAB-nodes (i.e., small bases stations (SBSs)), respectively [5]- [7]. Although IABbased cellular networks are envisioned to meet the increase in user and traffic demands, the mutual interference between access and backhaul links and the limitations of backhaul capacity are among the main challenges to develop reliable communication links in IAB networks (see, e.g., [5]).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge lies in the newly introduced cross-tier interference by spectrum sharing between the access and backhaul links. Recently, several research efforts have been made to address the resource management issue for full-duplex self-backhauled wireless networks [7]- [10]. The authors in [7] demonstrated that compared with a conventional time-division duplex (TDD)/frequency-division duplex (FDD) self-backhauled network, the downlink rate in the full-duplex of relays, and the relay clusters of the destinations can overlap with each other.…”
Section: Introductionmentioning
confidence: 99%